Analisis Perbandingan Persepsi Tenaga Non PNS Mengenai Profesionalisme Pada Instansi BLUD Dan OPD Di Kutai Kartanegara (Studi Kasus Pada RSUD A.M Parikesit Dan Dinas Pekerjaan Umum) - Dayang Dessy Nurhayati; Awang Yacoub Luthman; Dedy Mulyadi (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract:The purpose of this study was to find out whether there were differences in the professionalism of work of Non PNS employees at BLUD Institutions with OPD in Kutai Kartanegara. The data used is primary data. This research method uses incidental sampling. The sample studied was 86 respondents in BLUD and 52 respondents in OPD. The number of variables studied is 1 namely work professionalism with 5 indicators. In this study, the Independent Sample T-Test Test was analyzed by comparing the mean values of BLUDs and OPDs in Kutai Kartanegara. From the results of the study stated that the statement of the first hypothesis in this study which states